Application of cryogenic detectors in time-of-flight mass spectrometry of large biomolecules; Verhandlungen der Deutschen Physikalischen Gesellschaft; Bd. 40, № 2 - Uchaykin (Uchaikin) S. V. Sergey Victorovich; Christ P.; Rutzinger S.; Seidel W.; Proebst F. (2005, 2005)
Microchannel plates (MCP) which are used as detectors in conventional time-of-flight mass spectrometers exhibit a very good performance for small ion masses up to about 20 kDa. Due to their detection mechanism the sensitivity of MCP's decreases drastically for very large and, accordingly, very slow molecules. Cryogenic calorimeter are extremely sensitive particle detectors. They combine a 100% detection efficiency, which is impact independent of the velocity of the molecule, with energy resolution and a low threshold. Thus, a very high and mass-independent detection sensitivity is expected from their application in time-of-flight mass spectrometry. We implemented a cryogenic calorimeter with a superconducting phase transition thermometer in a dual reflector time-of-flight mass spectrometer. In a dilution series, using standard sample preparation procedure, we could show that the detection limit of insulin can be decreased by several orders of magnitude, down to below 1 amol total amount on the target.